The June Offensive: The Impact of the June Offensive on the Russian Revolution - Kooken, Nathan (The Toro Historical Review, 2021)
This essay explores the relations between soldiers, officers, command staff, and the Provisional Government, to explain why and how the June Offensive of 1917 failed, and to investigate its effects on the Russian Revolution. The liberals and moderate socialists of the Provisional Government failed to compose a coherent policy on the war and on soldiers' rights, resulting in extreme social and political polarization. Proclaiming the policy of revolutionary defensism, prosecuting a strictly defensive war, and seeking peace without annexations or indemnities, the Provisional Government contradictorily launched the June Offensive. The June Offensive was a central point in the Russian Revolution, marking the breakdown of democratic consensus and contributing to the disintegration of the armed forces, the collapse of social order, and the rise of the Bolsheviks.